(untitled) (Western European Journal of Historical Events and Social Science, 2025)
The development of the transport infrastructure of the Republic of Uzbekistan, the emergence of a modern transport system, stabilization of the economy, the formation of a national transport system, the influence of highways on the economic development of the country